Optimization of culture of Leptospira from humans with leptospirosis - Vanaporn Wuthiekanun (2018)
A prospective study of 989 patients with acute febrile illness was performed in northeast Thailand to define the yield of Leptospira from four different types of blood sample. Based on a comparison of the yields from whole blood, surface plasma, deposit from spun plasma, and dotted blood samples from 80 patients with culture-proven leptospirosis, we suggest a sampling strategy in which culture is performed using whole blood and deposit from spun plasma. Copyright © 2007, American Society for Microbiology. All Rights Reserved.